Use of benzodiazepines in the city of Porteirao, Goias, Brazil - Costa, Renata Silva Oliveira (2022)
Benzodiazepines (BZD), as they are considered safe drugs, are among the most consumed controlled drug classes worldwide. They are anxiolytics and hypnotics, mainly indicated for the treatment of anxiety and insomnia. They should be used in the acute phase of symptoms, that is, at the beginning of treatment. This study aimed to analyze the profile of benzodiazepine users in a private pharmacy in the city of Porteirão. A field research was carried out in July and August 2021, through interviews in a questionnaire format, with users of BZD, during the purchase of the drug. The results of this research show that most users of this drug class are female, between 18 and 59 years old, with no education, with low purchasing power. They are drugs prescribed by psychiatrists and general practitioners for cases of anxiety and insomnia. The period of use of the drug is longer than recommended in the literature, that is, it is inappropriately used. Clonazepam and alprazolam are the most used medications according to clinical prescriptions. Benzodiazepines have proven their effectiveness as long as the treatment is followed up periodically to intervene whenever necessary, in order to avoid health risks.